Working and ageing : emerging theories and empirical perspectives - (:unkn) unknown (Publications Office of the European Union, 2010)
"Reviewing current research literature and presenting new empirical findings, the contributions in this book reflect the ways in which retirement and an ageing workforce are at the intersection of key social changes over recent decades. It addresses the question of what factors enable, or hamper, people to continue working at advanced age; it aims to provide sound and accessible evidence and suggest innovative ways of thinking to support active ageing policies. The book is divided into four parts. By examining emerging career development concepts and learning frameworks for ageing workers, the first part gives a broad view of the subject matter. The second part provides perspectives from comparative cross-national research on ageing, learning and working in Europe. The third part identifies ways of breaking traditional patterns to extend working lives and to assist working beyond retirement age. In the final part, active ageing is approached by considering the role of guidance and employer-supported initiatives." (Herausgeber, BIBB-Doku)
Keywords: G 1.1.1 Demografie; G 1.2 Arbeitsmarkt; P 1.8 Ältere; I 2.2 Europa; Demografischer Wandel; Arbeitswelt; Arbeitsmarkt; Älterer Arbeitnehmer; Lebenslanges Lernen; Berufliche Weiterbildung; Personalentwicklung; Personalmanagement; Europa